Development and application of radar reflectometer using micro to infrared waves. Issue 1 (1st January 2018) - Mase, A.; Kogi, Y.; Kuwahara, D.; Nagayama, Y.; Ito, N.; Maruyama, T.; Ikezi, H.; Wang, X.; Inutake, M.; Tokuzawa, T.; Kohagura, J.; Yoshikawa, M.; et al.
Abstract: Progress in microwave and millimeter-wave technologies has made possible advanced diagnostics for application to various fields, including radio astronomy, alien substance detection, plasma diagnostics, airborne and space-borne imaging radars called as synthetic aperture radars, and living body measurements. Transmission, reflection, scattering, and radiation processes of electromagnetic waves are utilized as diagnostic principles. The diagnostics are classified as active and passive systems. Specifically, active radar reflectometry has become of importance in various applications due to the possibility of high localization and accessibility of the measurements as well as the non-invasive nature of the systems. In this paper, recent development and application of radar reflectometers are described. The key words are profile reflectometry, fluctuation reflectometry, imaging radar (optics imaging and synthetic aperture imaging), and radio-optics fusion technology in order to improve the spatial resolution. Abstract :